Percutaneous Transhepatic Biliary Drainage as a Viable Alternative to Failed Endoscopic Retrograde Cholangiopancreatography in Hepatobiliary Disorders: A Retrospective Analysis: Alternative in Hepatobiliary Disorders - Asadullah, Muhammad; Naz, Nasreen; Sattar, Amjad; Al Qamari, Nauman; Ahmed, Parvez; Ahmed, Zahoor (Pakistan Journal of Health Sciences, 2024)
The conventional second-line treatment for failed ERCP was Percutaneous Transhepatic Biliary Drainage (PTBD). Because of its high level of success and accessibility, PTBD has evolved into a well-established rescue therapy. Objective: To assess the procedural outcomes of PTBD following a failed ERCP in patients with hepatobiliary disorders. Additionally, it was focused on finding the significant factors that impact PTBD outcomes. Methods: A retrospective descriptive analysis was performed on 128 individuals at Dow Hospital Ojha Campus Karachi, who received PTBD following a failed ERCP. Between January 2023 and March 2024, we evaluated the clinical success rate, post-PTBD complications, and mortality. Results: The mean age of the patients was 65.9+/-11.7 years, and 76 (59.4%) patients were female. The clinical success rate was 77.3%, and complications after PTBD were 20(15.6%). A prolonged hospital stay was reported in 29 (22.7%) patients, and 13 (10.2%) patients died within 30 days. Younger age, etiology, and type of PTBD had a significant association with clinical success (P<0.05). Older age, female patients, and malignant etiology had a higher complication rate and mortality (P<0.05). Conclusions: PTBD provides a safe, effective, and viable alternative approach for patients with hepatobiliary disorders. It has a low rate of complications, a high rate of procedural success, and a low risk of mortality after a failed ERCP. Adverse events were more common in patients with a malignant etiology, older age, and female gender.